Preparation method of substrate with multi-level porous coating and catalyst carrier and equipment
Through microarc oxidation technology, the multi-stage pore coating is formed in the preparation of multi-stage pore materials, which solves the problems of complex preparation processes, high cost and environmental pollution in the prior art, and achieves efficient and environmentally friendly multi-stage pore materials preparation.
Patent Information
- Application Number
- CN202411971388.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The preparation process of existing multi-stage pore materials is complex, has high cost, and is difficult to control the pore structure. The commonly used preparation methods have problems of environmental pollution and health hazards.
A multi-stage pore coating is prepared by micro-arc oxidation technology, and a multi-stage pore structure is formed by placing the matrix in an electrolyte including sodium silicate, sodium tetraborate and sodium hydroxide.
The preparation process of multi-stage pore materials is simplified, the cost is reduced, the environmental protection of the preparation process is improved, and the pore structure can be finely regulated, and the porosity and specific surface area can be improved.
Smart Images

Figure CN119753782A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of surface engineering technology, for example, to a method for preparing a substrate with a multi-level porous coating and a catalyst carrier and equipment. Background Art
[0002] Hierarchical porous materials have the advantages of high porosity, large specific surface area, low thermal conductivity, low volume density and stable chemical properties. They have broad application prospects in adsorption and separation, catalyst carriers, thermal insulation materials, energy storage, sensors and other fields.
[0003] Based on the size of the pore diameter, porous materials are divided into three categories: macroporous materials with pore diameters greater than 50nm, mesoporous materials with pore diameters between 2nm and 50nm, and microporous materials with pore diameters less than 2nm. Multi-level porous materials mainly include macroporous-mesoporous materials, microporous-mesoporous materials, and mesoporous-mesoporous materials containing two or more different pore diameters.
[0004] Common preparation methods for macroporous-mesoporous materials include template method, foaming method, sol-gel method and molten salt method. Among them, the combustion of organic templates in the template method is easy to pollute the environment; the pore size of the material prepared by the foaming method is not easy to control. The preparation process of the sol-gel method is complicated and the synthesis cost is high. The volatilization of molten salt in the molten salt method seriously endangers human health and pollutes the environment, and the impurity content of the obtained product is high and the yield is low. It can be seen that there are still many problems in the preparation of multi-level porous materials, and their synthesis process usually involves two or more methods, the preparation process is complicated, the preparation cost is high, and the pore structure is difficult to control. Summary of the invention
[0005] In order to provide a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. The summary is not an extensive review, nor is it intended to identify key / critical components or delineate the scope of protection of these embodiments, but rather serves as a prelude to the detailed description that follows.
[0006] The embodiments of the present disclosure provide a method for preparing a substrate with a multi-level porous coating, a catalyst carrier, and an apparatus, which simplify the preparation process of the multi-level porous material and reduce the preparation cost. In addition, the multi-level porous coating is prepared by micro-arc oxidation technology. The preparation method is green and efficient, and the environmental protection effect is improved.
[0007] In some embodiments, a method for preparing a substrate with a multi-level porous coating is provided, comprising: placing the substrate in a first electrolyte, using the substrate as an anode and stainless steel as a cathode, and performing a first micro-arc oxidation treatment to obtain the multi-level porous coating; wherein the components of the first electrolyte include sodium silicate, sodium tetraborate and sodium hydroxide.
[0008] In some embodiments, a catalyst carrier is provided, comprising: a catalyst carrier prepared by the preparation method of the multi-level porous functional coating described in any of the above embodiments.
[0009] In some embodiments, a device using the catalyst carrier described in any of the above embodiments is provided.
[0010] The preparation method of the substrate with the multi-level porous coating, the catalyst carrier, and the device provided in the embodiments of the present disclosure can achieve the following technical effects:
[0011] The preparation method of the multi-level porous coating provided by the present disclosure comprises placing a substrate in a first electrolyte, using the substrate as an anode and stainless steel as a cathode, and performing micro-arc oxidation treatment to obtain the multi-level porous coating, wherein the components of the first electrolyte include sodium silicate, sodium tetraborate and sodium hydroxide.
[0012] The present invention adopts micro-arc oxidation technology to prepare multi-level porous coatings. Compared with the method of preparing multi-level porous materials in the related art, the micro-arc oxidation technology does not need to use expensive template materials and complex post-processing processes, simplifies the preparation process flow, and reduces the preparation cost of the multi-level porous coating. In addition, the micro-arc oxidation technology is an environmentally friendly preparation method. No harmful chemicals are required in the process, and less waste is generated in the process, which is easy to handle, reducing environmental pollution and improving the environmental protection effect.
[0013] Furthermore, the porosity of the micro-arc oxidation technology is adopted, and the micro-arc oxidation treatment is carried out using a first electrolyte including sodium silicate, sodium tetraborate and sodium hydroxide. The sodium silicate in the first electrolyte can provide silicate ions, and the silicate ions can promote the formation and expansion of pores during the high temperature and high pressure micro-arc oxidation discharge process. Sodium tetraborate is added to the first electrolyte, and sodium tetraborate can provide borate ions in the first electrolyte, which can improve the stability of the first electrolyte. In addition, the borate ions react with metal ions during the micro-arc oxidation process to form borates with certain solubility, and the borates can adjust the pore size in the discharge channel and promote the formation of a multi-level pore structure. Sodium hydroxide makes the first electrolyte alkaline. Under alkaline conditions, the oxidation reaction of the metal is easier to proceed, which can promote the oxidation reaction to form an oxide coating during the micro-arc oxidation process and form pores in the discharge channel.
[0014] In this way, the micro-arc oxidation technology is used in combination with the components of the first electrolyte to promote the formation of a multi-level pore structure during the micro-arc oxidation process, so that the coating can produce pores of different sizes and shapes during the formation process, thereby obtaining a multi-level pore structure with high porosity.
[0015] The above general description and the following description are exemplary and explanatory only and are not intended to limit the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] One or more embodiments are exemplarily described by corresponding drawings, which do not limit the embodiments. Elements with the same reference numerals in the drawings are shown as similar elements, and the drawings do not constitute a scale limitation, and wherein:
[0017] Figure 1 This is a SEM image of a coating prepared by using a mixed electrolyte prepared by sodium silicate, sodium tetraborate and sodium hydroxide in one embodiment of the present disclosure;
[0018] Figure 2 is the SEM image of the coating prepared using a single silicate electrolyte;
[0019] Figure 3 is the SEM image of the coating prepared using a single sodium tetraborate electrolyte;
[0020] Figure 4 yes Figure 1 A magnified view of the multi-level porous coating in the SEM image of the coating shown;
[0021] Figure 5 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 5 g / L of sodium silicate and a mass concentration of 5 g / L of sodium tetraborate;
[0022] Figure 6 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 5 g / L of sodium silicate and a mass concentration of 10 g / L of sodium tetraborate;
[0023] Figure 7 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 10 g / L of sodium silicate and a mass concentration of 10 g / L of sodium tetraborate;
[0024] Figure 8 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 5 g / L of sodium silicate and a mass concentration of 15 g / L of sodium tetraborate;
[0025] Fig. 9 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 10 g / L of sodium silicate and a mass concentration of 15 g / L of sodium tetraborate;
[0026] Fig.10 This is a SEM image of a coating prepared in an embodiment of the present disclosure, in which the electrolyte used has a mass concentration of 15 g / L of sodium silicate and a mass concentration of 15 g / L of sodium tetraborate;
[0027] Fig.11 is a SEM image of a multi-level porous coating obtained in an embodiment of the present disclosure when the electrolyte is at 10°C;
[0028] Fig.12 is a SEM image of a multi-level porous coating obtained in a comparative example when the electrolyte is at 20°C;
[0029] Fig.13 is a SEM image of a multi-level porous coating obtained in another comparative example when the electrolyte is at 50°C;
[0030] Fig.14 is a SEM image of a multi-level porous coating obtained in another comparative example when the electrolyte is at 80°C;
[0031] Fig.15 is a SEM image of a coating prepared by a method for preparing a substrate with a multi-level porous coating provided by an embodiment of the present disclosure;
[0032] Fig.16 is a SEM image of a coating prepared by a method for preparing a substrate with a multi-level porous coating provided by another embodiment of the present disclosure;
[0033] Fig.17 is a SEM image of a coating prepared by a method for preparing a substrate with a multi-level porous coating provided by another embodiment of the present disclosure;
[0034] Fig.18 is a SEM image of a coating prepared by a method for preparing a substrate with a multi-level porous coating provided by another embodiment of the present disclosure;
[0035] Fig.19 is a SEM image of a coating prepared by a method for preparing a substrate with a multi-level porous coating provided by another embodiment of the present disclosure;
[0036] Fig. 20 yes Fig.19 EDS scanning image of the coating of the embodiment shown in the TEM;
[0037] Fig.21 is a SEM image of a coating prepared in another comparative example;
[0038] Fig. 22 yes Fig.21 The EDS scanning image of the coating prepared in the comparative example shown is taken under TEM. DETAILED DESCRIPTION
[0039] In order to be able to understand the features and technical contents of the embodiments of the present disclosure in more detail, the implementation of the embodiments of the present disclosure is described in detail below in conjunction with the accompanying drawings. The attached drawings are for reference only and are not used to limit the embodiments of the present disclosure. In the following technical description, for the convenience of explanation, a full understanding of the disclosed embodiments is provided through multiple details. However, one or more embodiments can still be implemented without these details. In other cases, to simplify the drawings, well-known structures and devices can be simplified for display.
[0040] The terms "first", "second", etc. in the specification and claims of the embodiments of the present disclosure and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so as to describe the embodiments of the embodiments of the present disclosure described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0041] In the embodiments of the present disclosure, the terms "upper", "lower", "inside", "middle", "outside", "front", "back" and the like indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. These terms are mainly intended to better describe the embodiments of the present disclosure and their embodiments, and are not intended to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction. Moreover, in addition to being used to indicate directions or positional relationships, some of the above terms may also be used to indicate other meanings. For example, the term "upper" may also be used to indicate a certain dependency or connection relationship in certain circumstances. For those of ordinary skill in the art, the specific meanings of these terms in the embodiments of the present disclosure can be understood according to specific circumstances.
[0042] In addition, the terms "disposed", "connected", and "fixed" should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present disclosure can be understood according to specific circumstances.
[0043] Unless otherwise stated, the term "plurality" means two or more.
[0044] In the embodiment of the present disclosure, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B indicates: A or B.
[0045] The term "and / or" is a description of the association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or, A and B.
[0046] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present disclosure may be combined with each other.
[0047] In some embodiments, a method for preparing a substrate with a multilevel porous coating is provided, wherein the substrate is placed in a first electrolyte, and micro-arc oxidation treatment is performed using the substrate as an anode and stainless steel as a cathode to obtain the multilevel porous coating, wherein the components of the first electrolyte include sodium silicate, sodium tetraborate and sodium hydroxide.
[0048] The present invention adopts micro-arc oxidation technology to prepare multi-level porous coatings. Compared with the method of preparing multi-level porous materials in the related art, the micro-arc oxidation technology does not need to use expensive template materials and complex post-processing processes, simplifies the preparation process flow, and reduces the preparation cost of the multi-level porous coating. In addition, the micro-arc oxidation technology is an environmentally friendly preparation method. No harmful chemicals are required in the process, and less waste is generated in the process, which is easy to handle, reducing environmental pollution and improving the environmental protection effect.
[0049] Furthermore, the porosity of the micro-arc oxidation technology is adopted, and the micro-arc oxidation treatment is carried out using a first electrolyte including sodium silicate, sodium tetraborate and sodium hydroxide. The sodium silicate in the first electrolyte can provide silicate ions, and the silicate ions can promote the formation and expansion of pores during the high temperature and high pressure micro-arc oxidation discharge process. Sodium tetraborate is added to the first electrolyte, and sodium tetraborate can provide borate ions in the first electrolyte, which can improve the stability of the first electrolyte. In addition, the borate ions react with metal ions during the micro-arc oxidation process to form borates with certain solubility, and the borates can adjust the pore size in the discharge channel and promote the formation of a multi-level pore structure. Sodium hydroxide makes the first electrolyte alkaline. Under alkaline conditions, the oxidation reaction of the metal is easier to proceed, which can promote the oxidation reaction to form an oxide coating during the micro-arc oxidation process and form pores in the discharge channel.
[0050] In this way, the micro-arc oxidation technology is used in combination with the components of the first electrolyte to promote the formation of a multi-level pore structure during the micro-arc oxidation process, so that the coating can produce pores of different sizes and shapes during the formation process, thereby obtaining a multi-level pore structure with high porosity.
[0051] Optionally, before placing the substrate in the first electrolyte, the method further includes: pre-treating the substrate.
[0052] Optionally, the step of pre-treating the substrate includes: degreasing the substrate with acetone, then ultrasonically cleaning the substrate with anhydrous ethanol, and then drying the substrate.
[0053] In this embodiment, acetone is used to degrease the substrate to remove oil stains on the substrate surface, improve the bonding between the coating and the substrate, and facilitate the subsequent growth of the coating. Anhydrous ethanol is used to clean the substrate in an ultrasonic cleaning machine to remove residual acetone to prevent adverse effects on the micro-arc oxidation process. A hair dryer is used to dry the substrate in preparation for the subsequent micro-arc oxidation treatment.
[0054] Optionally, the mass concentration of each component in the first electrolyte is as follows: the mass concentration of sodium silicate ranges from 5 g / L to 15 g / L, the mass concentration of sodium tetraborate ranges from 5 g / L to 15 g / L, and the mass concentration of sodium hydroxide ranges from 1 g / L to 3 g / L.
[0055] In this embodiment, by reasonably configuring the mass concentrations of sodium silicate, sodium tetraborate and sodium hydroxide in the first electrolyte to change the dissolution and deposition rates of the coating, a coating with a uniform multi-level pore structure is formed, the specific surface area and porosity of the coating are increased, thereby improving the catalytic, adsorption and other properties of the coating.
[0056] Wherein, the mass concentration of sodium silicate ranges from 5g / L to 15g / L. When the mass concentration of sodium silicate is within the range of 5g / L to 15g / L, the deposition of silicon-based oxides in the micro-arc oxidation process can be effectively promoted to form a multi-level pore structure. Appropriate sodium silicate concentration helps to improve the compactness and mechanical strength of the coating, while ensuring that the coating has good porosity. If the sodium silicate concentration is too low, the coating structure may be uneven and the porosity may be low. If the concentration is too high, the coating may be too thick and the pores may be too large, affecting the performance of the coating. Wherein, the specific value of the mass concentration of sodium silicate includes but is not limited to: 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L or 15g / L.
[0057] The mass concentration of sodium tetraborate ranges from 5 g / L to 15 g / L. Sodium tetraborate can stabilize the pH value of the solution, increase the ionic strength of the solution, and promote the micro-arc oxidation process in the first electrolyte. The mass concentration of sodium tetraborate is within the concentration range of 5 g / L to 15 g / L, which helps to form a uniform and stable multi-level pore structure and improve the uniformity and stability of the coating. An appropriate amount of sodium tetraborate can also improve the corrosion resistance and wear resistance of the coating. Improper concentration may cause the coating structure to be unstable or affect other properties of the coating, such as corrosion resistance. Among them, the specific values of the mass concentration of sodium tetraborate include but are not limited to: 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L or 15 g / L.
[0058] The mass concentration of sodium hydroxide ranges from 1 g / L to 3 g / L. Sodium hydroxide is used to adjust the pH value of the solution in the first electrolyte, affecting the discharge behavior and coating formation during micro-arc oxidation. The mass concentration of sodium hydroxide is within the concentration range of 1 g / L to 3 g / L, and sodium hydroxide can optimize the discharge characteristics during micro-arc oxidation and promote the formation of a multi-level pore structure. An appropriate sodium hydroxide concentration helps to improve the porosity and specific surface area of the coating, thereby enhancing the catalytic or adsorption properties of the coating. Too low or too high a sodium hydroxide concentration may affect the pore structure of the coating, resulting in a decrease in coating performance. Among them, the specific values of the mass concentration of sodium hydroxide include but are not limited to: 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L or 3 g / L.
[0059] Optionally, the ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate ranges from 0.33 to 3.
[0060] In this embodiment, when the mass concentration ratio of sodium silicate to sodium tetraborate is in the range of 0.33 to 3, the pore structure formed during the micro-arc oxidation process is optimized by reasonably setting the mass concentration ratio of sodium silicate to sodium tetraborate. By adjusting the mass concentration ratio of sodium silicate to sodium tetraborate, the discharge process is regulated, thereby achieving fine regulation of the coating structure and morphology, which helps to form a multi-level pore structure of appropriate size and uniform distribution, thereby increasing the specific surface area and porosity of the coating.
[0061] Optionally, the specific value of the ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate includes but is not limited to: 0.33, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8 or 3.
[0062] Optionally, the ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is in the range of 0.5 to 1.5. The pore structure formed during the micro-arc oxidation process can be optimized by reasonably setting the mass concentration ratio of sodium silicate to sodium tetraborate.
[0063] Optionally, the preparation method of the first electrolyte includes: adding sodium silicate, sodium tetraborate and sodium hydroxide into a solvent, and continuously stirring for a set time to obtain the first electrolyte.
[0064] In this embodiment, sodium silicate, sodium tetraborate and sodium hydroxide are added to the solvent and stirred continuously to ensure that the electrolyte is uniformly dispersed in the solution. By continuously stirring for a set time, the solute in the first electrolyte is fully dissolved and mixed evenly, and the prepared colloidal solution is stable. By preparing a first electrolyte with uniform and stable composition, the micro-arc oxidation process is facilitated, and a coating with a uniform multi-level pore structure is formed, thereby increasing the specific surface area and porosity of the coating.
[0065] Optionally, the solvent is selected from at least one of deionized water and pure water.
[0066] Optionally, the set stirring time can be determined according to the dosage of the first electrolyte, so that the solute in the obtained first electrolyte is fully dissolved and mixed evenly.
[0067] Optionally, the step of performing the first micro-arc oxidation treatment includes: processing for a first preset time length using a preset pulse processing method according to a first preset current, a first preset duty cycle and a first preset frequency.
[0068] In this embodiment, by performing micro-arc oxidation treatment according to a first preset current, a first preset duty cycle, a first preset frequency and a first preset duration, the formation process of the coating can be precisely controlled to precisely control the pore size, distribution and thickness of the coating. By precisely adjusting these electrical parameters and electrolyte components, a multi-level porous ceramic coating with a predetermined pore size, distribution and porosity can be generated on the substrate surface.
[0069] Optionally, the preset pulse processing mode includes: a unipolar pulse output mode or a bipolar pulse output mode. The value range of the first preset current is: 0.7A to 2.0A. And / or, the value range of the first preset duty cycle is: 5% to 40%. And / or, the value range of the first preset frequency is: 100Hz to 1000Hz. And / or, the value range of the first preset duration is: 5min to 40min.
[0070] In this embodiment, the preset pulse processing mode includes: a unipolar pulse output mode or a bipolar pulse output mode. The specific processing mode can be selected according to the requirements of the multi-level holes of the coating.
[0071] For those with high porosity requirements, the unipolar pulse output mode can be selected. The single pulse discharge energy of the unipolar pulse output mode is large, which can make the coating produce more pores. For those with relatively low porosity requirements, the bipolar pulse output mode can be used. The bipolar pulse output mode can form a more complex pore structure in the coating, and the density is higher than that of the unipolar pulse output mode.
[0072] Furthermore, the magnitude of the current directly affects the discharge intensity and the formation of the pore structure during the micro-arc oxidation process. By setting the value range of the first preset current to: 0.7A to 2.0A, the formation of multi-level pores in the coating can be promoted. At the same time, it is avoided that the coating is damaged due to excessive discharge of current, and the pore size and porosity are small due to too small current. Among them, the specific values of the first preset current include but are not limited to: 0.7A, 0.8A, 0.9A, 1.0A, 1.1A, 1.2A, 1.3A, 1.4A, 1.5A, 1.6A, 1.7A, 1.8A, 1.9A or 2.0A.
[0073] Furthermore, the duty cycle refers to the ratio of the pulse on time to the pulse period, and the duty cycle affects the growth rate and pore structure of the coating. By adjusting the duty cycle, the growth rate and pore size of the coating can be controlled to optimize the performance of the coating. If the preset duty cycle is too large, there will be too many large pores, and if the preset duty cycle is too small, there will be more small pores. Therefore, by first setting the value range of the preset duty cycle to: 5% to 40%, the porosity and the pore distribution of large and small pores can be improved. Among them, the specific values of the first preset duty cycle include but are not limited to: 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30%, 32%, 35%, 37% or 40%.
[0074] Furthermore, frequency refers to the number of times the pulse current is repeated per unit time. Frequency affects the discharge frequency and the formation rate of the coating during micro-arc oxidation. By setting a suitable preset frequency, the stability of the coating formation can be improved. Too high a frequency will result in a short pulse interval, smaller pores formed on the coating surface, and lower porosity. Too low a frequency will result in a long pulse interval, resulting in too many larger pores. By setting the value range of the first preset frequency to: 100Hz to 1000Hz, the growth rate and shape of the pores in the coating can be increased, and the stability of the coating formation can be improved. Among them, the specific values of the first preset frequency include but are not limited to: 100Hz, 150Hz, 200Hz, 250Hz, 300Hz, 350Hz, 400Hz, 450Hz, 500Hz, 550Hz, 600Hz, 650Hz, 700Hz, 750Hz, 800Hz, 8500Hz, 900Hz, 950Hz or 1000Hz.
[0075] Furthermore, the preset duration is the duration of the micro-arc oxidation process, and the preset duration determines the time for the coating to grow, thereby affecting the thickness and pore structure of the coating. By setting the value range of the first preset duration to: 5min to 40min, it is ensured that the coating reaches the required thickness and porosity. If the first preset duration is too long, the coating will be thicker and the pores will be deeper, which may cause the coating structure to be too loose. If the first preset duration is too short, it will affect the formation of pores, resulting in excessive density of the coating and reduced porosity. Among them, the specific values of the first preset duration include but are not limited to: 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 20min, 22min, 25min, 27min, 30min, 32min, 35min, 37min or 40min.
[0076] Optionally, the temperature of the first electrolyte is less than or equal to 10°C.
[0077] In this embodiment, during the micro-arc oxidation process, the temperature of the first electrolyte is less than or equal to 10° C., so that the first electrolyte is in a low temperature state. The first electrolyte in a low temperature state can improve the stability of the chemical reaction, slow down the melting and recondensation speed of the coating material during the micro-arc oxidation process, and thus facilitate the formation of a multi-level pore structure.
[0078] In some examples, the temperature of the first electrolyte is maintained by placing a container containing the first electrolyte in a low-temperature thermostatic bath and setting the temperature in the low-temperature thermostatic bath to below 10° C. During the micro-arc oxidation process, the first electrolyte is kept in a continuously stirred state to improve the uniformity of the temperature of the first electrolyte.
[0079] Optionally, the substrate includes a foamed aluminum substrate. The foamed aluminum substrate itself has a porous structure, which can be used as a template during the micro-arc oxidation process, so that the final coating can maintain or even increase the porosity, thereby obtaining a high-porosity multi-level porous coating. The porous structure of the foamed aluminum substrate greatly increases the specific surface area of the coating. The specific surface area of the multi-level porous coating prepared using the foamed aluminum substrate is as high as 56200m 2 / m 3 , especially suitable for high-demand applications with large specific surface area, such as catalyst carriers, adsorption materials, etc. In addition, the porous structure of the foam aluminum substrate can provide more anchor points, making the multi-level porous coating and the substrate metallurgically bonded, more firmly, and improving the adhesion of the coating.
[0080] Optionally, the substrate includes an aluminum alloy substrate or a magnesium alloy substrate.
[0081] In this embodiment, the substrate includes but is not limited to a foamed aluminum substrate, an aluminum alloy substrate or a magnesium alloy substrate. The foamed aluminum substrate, the aluminum alloy substrate or the magnesium alloy substrate all have good mechanical properties and corrosion resistance, and as a substrate, can provide a good coating adhesion surface. In addition, the multi-level porous coating has a strong bonding force with these substrate materials, which helps the coating to remain stable during long-term use and is not easy to fall off. The application of different substrate materials allows the multi-level porous coating to adapt to different working environments and application requirements. For example, the foamed aluminum substrate is suitable for applications requiring a high specific surface area, while the aluminum alloy or magnesium alloy substrate is suitable for occasions requiring light weight and high strength.
[0082] Optionally, after obtaining the multilevel porous coating, the preparation method further comprises: placing the substrate with the multilevel porous coating as an anode in a second electrolyte, using stainless steel as a cathode, and performing micro-arc oxidation treatment again to obtain the multilevel porous functional coating.
[0083] The components of the second electrolyte include sodium silicate, sodium tetraborate, sodium hydroxide and functional components.
[0084] In this embodiment, the preparation method is divided into two steps. In the first step, a multi-level porous coating is prepared. In the second step, the multi-level porous coating is used as an anode, placed in a second electrolyte, and subjected to micro-arc oxidation treatment using stainless steel as a cathode to obtain a multi-level porous functional coating.
[0085] In this way, the micro-arc oxidation technology is used, combined with the components of the first electrolyte and the second electrolyte, to promote the formation of a multi-level pore structure during the micro-arc oxidation process, so that the coating can produce pores of different sizes and shapes during the formation process, thereby obtaining a multi-level pore structure with high porosity. Moreover, on the basis of the multi-level pore base layer, the functional components are adsorbed on the outside of the coating and inside the pores to prepare a multi-level pore functional coating, which improves the functional effect and has a high porosity.
[0086] Optionally, the step of preparing the second electrolyte includes: adding deionized water, sodium silicate, sodium tetraborate and sodium hydroxide to the first container, and continuously stirring for a second time to obtain a first reserve solution. Adding deionized water, ethylene glycol, triethanolamine and nano-titanium dioxide to the second container, and performing constant temperature ultrasonic aging for a third time to obtain a second reserve solution. Mixing the first reserve solution and the second reserve solution, and continuously stirring for a fourth time to obtain a second electrolyte.
[0087] In this embodiment, the steps of configuring the second electrolyte are divided into three steps, as follows: the first step is to prepare the first standby solution. Deionized water is used as a solvent to effectively dissolve sodium silicate, sodium tetraborate and sodium hydroxide. By stirring, the dissolution process can be accelerated to ensure that the solute in the electrolyte is completely dissolved to form a uniform solution. The second step is to prepare the second standby solution. Deionized water is used as a solvent, and ethylene glycol, triethanolamine and nano titanium dioxide are added. Ultrasonic aging helps to evenly disperse nano titanium dioxide in the solution and improve its functionality in the electrolyte. Constant temperature conditions ensure the stability and repeatability of the aging process. The third step is to mix the first standby solution and the second standby solution. The first standby solution and the second standby solution are prepared separately to avoid affecting the stability of the components during the preparation process. Among them, the specific values of the second time length, the third time length and the fourth time length can be determined according to the dosage of the electrolyte, so that the solute in the obtained electrolyte is fully dissolved and mixed uniformly.
[0088] Optionally, the proportions of the components in the second electrolyte are as follows: the mass concentration of sodium silicate ranges from 5 g / L to 15 g / L, the mass concentration of sodium tetraborate ranges from 5 g / L to 15 g / L, the mass concentration of sodium hydroxide ranges from 1 g / L to 3 g / L. The mass concentration of the functional component ranges from 3 g / L to 8 g / L.
[0089] In this embodiment, by rationally configuring the mass concentrations of sodium silicate, sodium tetraborate and sodium hydroxide in the second electrolyte to change the dissolution and deposition rates of the coating, a coating with a uniform multi-level pore structure is formed, the specific surface area and porosity of the coating are increased, thereby improving the catalytic, adsorption and other properties of the coating.
[0090] Optionally, specific values of the mass concentration of sodium silicate in the second electrolyte include but are not limited to: 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L or 15g / L.
[0091] Optionally, specific values of the mass concentration of sodium tetraborate in the second electrolyte include but are not limited to: 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L or 15g / L.
[0092] Optionally, specific values of the mass concentration of sodium hydroxide in the second electrolyte include but are not limited to: 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L or 3 g / L.
[0093] Optionally, the mass concentration of the functional component in the second electrolyte ranges from 3 g / L to 8 g / L. An appropriate amount of the functional component can improve the uniform distribution of the functional component in the electrolyte and improve the consistency and quality of the electrolysis product.
[0094] Optionally, specific values of the mass concentration of the functional component include but are not limited to: 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L or 8 g / L.
[0095] Optionally, the ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate in the second electrolyte is in the range of 0.33 to 3. The pore structure formed during the micro-arc oxidation process is optimized by reasonably setting the mass concentration ratio of sodium silicate to sodium tetraborate.
[0096] Optionally, the specific value of the ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate in the second electrolyte includes but is not limited to: 0.33, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 1.9, 2.0, 2.2, 2.4, 2.6, 2.8 or 3.
[0097] Optionally, the components of the second electrolyte further include: ethylene glycol and triethanolamine. In the second electrolyte, the mass concentration of ethylene glycol ranges from 5 ml / L to 15 ml / L, and the mass concentration of triethanolamine ranges from 10 ml / L to 20 ml / L.
[0098] In this embodiment, the components of the second electrolyte include sodium silicate, sodium tetraborate, sodium hydroxide, functional components, ethylene glycol and triethanolamine. By adding an appropriate amount of ethylene glycol, the low temperature performance of the electrolyte is improved, the boiling point of the electrolyte is increased, the evaporation loss of the electrolyte at high temperature is reduced, the stability of the electrolyte is maintained, and the service life of the electrolyte is extended. By adding an appropriate amount of triethanolamine, the conductivity of the electrolyte is increased, ion migration is promoted, and the electrolysis efficiency is improved, and the stability and antioxidant properties of the electrolyte are improved.
[0099] Optionally, in the process of preparing the multi-level porous coating in two steps as a whole, the value range of the first preset time is set to: 5min to 15min, so as to ensure that the coating reaches the required thickness and porosity for the second micro-arc oxidation treatment to obtain a multi-level porous functional coating. If the preset time is too long, the coating will be thicker and the pores will be deeper, which may cause the coating structure to be too loose. If the preset time is too short, the formation of pores will be affected, resulting in excessive density of the coating and reduced porosity. In this embodiment, the specific values of the first preset time include but are not limited to: 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min or 15min.
[0100] Optionally, the step of performing a second micro-arc oxidation treatment includes: processing for a second preset time period using a preset pulse processing method according to a second preset current, a second preset duty cycle and a second preset frequency.
[0101] In this embodiment, by performing micro-arc oxidation treatment according to a second preset current, a second preset duty cycle, a second preset frequency, and a second preset duration, the formation process of the coating can be precisely controlled to precisely control the pore size, distribution, and thickness of the coating. By precisely adjusting these electrical parameters and electrolyte components, a multi-level porous ceramic coating with a predetermined pore size, distribution, and porosity can be generated on the substrate surface.
[0102] Optionally, the preset pulse processing method includes: a unipolar pulse output method or a bipolar pulse output method. The specific processing method can be selected according to the requirements of the multi-level holes of the coating.
[0103] Optionally, the second preset current ranges from 0.7A to 2.0A. And / or, the second preset duty cycle ranges from 5% to 40%. And / or, the second preset frequency ranges from 100Hz to 1000Hz. And / or, the second preset duration ranges from 10min to 20min.
[0104] Optionally, the magnitude of the second preset current directly affects the discharge intensity and the formation of the pore structure during the second micro-arc oxidation process. By setting the value range of the second preset current to: 0.7A to 2.0A, the formation of multi-level pores in the coating can be promoted. At the same time, it is avoided that the coating is damaged due to excessive discharge of current, and the pore size and porosity are small due to too small current. Among them, the specific values of the second preset current include but are not limited to: 0.7A, 0.8A, 0.9A, 1.0A, 1.1A, 1.2A, 1.3A, 1.4A, 1.5A, 1.6A, 1.7A, 1.8A, 1.9A or 2.0A.
[0105] Optionally, the porosity and the pore distribution of large and small pores are improved by setting the value range of the second preset duty cycle to: 5% to 40%. The specific value of the second preset duty cycle includes but is not limited to: 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 27%, 30%, 32%, 35%, 37% or 40%.
[0106] Optionally, by setting the value range of the second preset frequency to: 100 Hz to 1000 Hz, the growth rate and shape of the pores in the coating layer can be increased, and the stability of the coating layer formation can be improved. The specific value of the second preset frequency includes but is not limited to: 100 Hz, 150 Hz, 200 Hz, 250 Hz, 300 Hz, 350 Hz, 400 Hz, 450 Hz, 500 Hz, 550 Hz, 600 Hz, 650 Hz, 700 Hz, 750 Hz, 800 Hz, 8500 Hz, 900 Hz, 950 Hz or 1000 Hz.
[0107] Optionally, the second preset time is set to a value range of 10 min to 20 min to ensure that the coating reaches the desired thickness and porosity. If the preset time is too long, the coating will be thicker and the pores will be deeper, which may cause the coating structure to be too loose. If the preset time is too short, the formation of pores will be affected, resulting in excessive density of the coating and reduced porosity. The specific values of the second preset time include but are not limited to 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min.
[0108] Optionally, the temperature of the second electrolyte is less than or equal to 10°C.
[0109] In this embodiment, during the micro-arc oxidation process, the electrolyte is kept at a low temperature by keeping the temperature of the electrolyte less than or equal to 10° C. The low temperature electrolyte can improve the stability of the chemical reaction and slow down the melting and recondensation speed of the coating material during the micro-arc oxidation process, thereby facilitating the formation of a multi-level pore structure.
[0110] Optionally, the functional ingredient comprises titanium dioxide, copper oxide or zinc oxide.
[0111] In this embodiment, different functions are achieved by adding different functional components. The selection of the functional components is not limited to titanium dioxide, copper oxide or zinc oxide.
[0112] In some embodiments, a catalyst carrier is provided, comprising: a catalyst carrier prepared by the preparation method of the multi-level porous functional coating described in any of the above embodiments.
[0113] The catalyst carrier provided in the embodiments of the present disclosure is prepared by the preparation method of the multi-level porous functional coating described in any of the above embodiments, thereby providing a multi-level porous functional coating with high porosity. The multi-level porous functional coating has controllable pore size and distribution, which facilitates the contact between the catalyst and the reactants, improves the catalytic efficiency of the catalyst, and enhances its stability.
[0114] In some embodiments, a device using the catalyst carrier described in any of the above embodiments is provided.
[0115] Among them, the equipment using the catalyst carrier described in any of the above embodiments includes but is not limited to an air purifier or a sewage treatment device.
[0116] Example
[0117] The following examples more specifically describe the contents disclosed in the present application. These examples are intended for illustrative purposes only, since various modifications and changes within the scope of the contents disclosed in the present application will be apparent to those skilled in the art.
[0118] Example 1
[0119] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0120] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0121] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used with a positive current of 1.0A, a duty cycle of 35%, a frequency of 550Hz, and a processing time of 8min. The obtained coating was as follows Figure 1 shown.
[0122] Comparative Example 1
[0123] Foamed aluminum is used as the matrix. The electrolyte components include 10 g / L sodium silicate and 1 g / L sodium hydroxide.
[0124] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0125] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used with a positive current of 1.0A, a duty cycle of 35%, a frequency of 550Hz, and a processing time of 8min. The obtained coating was as follows Figure 2 shown.
[0126] Comparative Example 2
[0127] Foamed aluminum is used as the matrix. The electrolyte components include 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0128] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0129] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used with a positive current of 1.0A, a duty cycle of 35%, a frequency of 550Hz, and a processing time of 8min. The obtained coating was as follows Figure 3 shown.
[0130] Combination Figures 1 to 3 As shown, the SEM (Scanning electron microscope) image of the coating obtained by using micro-arc oxidation technology but using electrolytes of different components. It can be seen that the coating prepared by the mixed first electrolyte prepared by sodium silicate, sodium tetraborate and sodium hydroxide used in Example 1 has many porous adsorption structures on the surface, and there are large pores that penetrate, as well as small pores. In the coating prepared by the single sodium silicate electrolyte in Comparative Example 1, the silicate mainly forms a dense ceramic layer rather than a porous structure during the micro-arc oxidation process. Therefore, the multi-level porous adsorption structure of the coating prepared by the single silicate first electrolyte is less. The coating prepared by the single sodium tetraborate first electrolyte in Comparative Example 2 is only 1.7μm thick, indicating that the single sodium tetraborate first electrolyte is not conducive to the increase of the coating thickness. And most of the pores are closed, indicating that the holes formed during the micro-arc oxidation process have not been effectively opened, resulting in the porous structure inside the coating being disconnected.
[0131] It can be seen that the mixed first electrolyte prepared by using sodium silicate, sodium tetraborate and sodium hydroxide can dissolve the oxides produced by micro-arc oxidation under the interaction of sodium silicate, sodium tetraborate and sodium hydroxide, promote the development of porous structure, improve porosity and increase specific surface area. Figure 4 As shown, it is further shown that Figure 1 The enlarged view of the multi-level porous coating in the SEM image of the coating shown shows the size and distribution of the pores in the multi-level porous coating prepared by the preparation method disclosed in the present invention, as indicated by A and B in the figure. The image shows that there are large through pores, which can increase the specific surface area of the coating and improve its adsorption performance. The through pores also provide channels for the transmission of substances within the coating, which is very important for applications such as catalysis and filtration.
[0132] Examples 2 to 7 are examples of preparing coatings using the preparation method of the above examples at different ratios of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate.
[0133] Example 2
[0134] Aluminum foam is used as a matrix. The components of the electrolyte include 5 g / L sodium silicate, 5 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 1.
[0135] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0136] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in the figure below. Figure 5 shown.
[0137] Example 3
[0138] Aluminum foam is used as a matrix. The components of the electrolyte include 5 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 0.5.
[0139] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0140] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in the figure below. Figure 6 shown.
[0141] Example 4
[0142] Aluminum foam is used as a matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 1.
[0143] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0144] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in the figure below. Figure 7 shown.
[0145] Example 5
[0146] Aluminum foam is used as a matrix. The components of the electrolyte include 5 g / L sodium silicate, 15 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 0.33.
[0147] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0148] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in Figure 8 shown.
[0149] Example 6
[0150] Aluminum foam is used as a matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 0.67.
[0151] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0152] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in Fig. 9 shown.
[0153] Example 7
[0154] Aluminum foam is used as a matrix. The components of the electrolyte include 15 g / L sodium silicate, 15 g / L sodium tetraborate and 1 g / L sodium hydroxide. The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate is 1.
[0155] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0156] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 8min. The SEM image of the obtained coating is shown in Fig.10 shown.
[0157] Combination Figures 5 to 10From the SEM image of the coating shown, it can be seen that by adjusting the mass concentration ratio of sodium silicate to sodium tetraborate and the selection of specific values, the discharge process can be regulated, thereby achieving fine regulation of the coating structure and morphology, which helps to form a multi-level pore structure with appropriate size and uniform distribution, thereby increasing the specific surface area and porosity of the coating.
[0158] Example 8 and Comparative Examples 4 to 6 respectively provide examples of micro-arc oxidation treatments performed when the electrolyte is at different temperatures.
[0159] Example 8
[0160] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0161] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0162] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the treatment time was 15min. During the treatment, the electrolyte was kept at 10℃. The SEM image of the obtained coating is shown in the figure below. Fig.11 shown.
[0163] Comparative Example 4
[0164] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0165] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0166] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the treatment time was 15min. During the treatment, the electrolyte was kept at 20℃. The SEM image of the obtained coating is shown in the figure below. Fig.12 shown.
[0167] Comparative Example 5
[0168] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0169] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0170] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the treatment time was 15min. During the treatment, the electrolyte was kept at 50℃. The SEM image of the obtained coating is shown in the figure below. Fig.13 shown.
[0171] Comparative Example 6
[0172] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0173] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0174] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the treatment time was 15min. During the treatment, the electrolyte was kept at 80℃. The SEM image of the obtained coating is shown in the figure. Fig.14 shown.
[0175] Combination Figures 11 to 14 From the SEM images of the coating shown, it can be seen that the electrolyte temperature has a huge impact on the porosity of the coating. The electrolyte is in a low temperature state, and the surface of the obtained coating has abundant pores. As the electrolyte temperature increases, the number of pores on the surface of the coating becomes fewer and fewer, because high temperature causes the diffusion rate of substances in the first electrolyte to accelerate, making the coating material easier to melt and quickly recondense during the discharge process, thereby closing some of the pores. Therefore, by keeping the electrolyte temperature below 10°C, a large number of pores can be formed during the micro-arc oxidation process, thereby increasing the specific surface area and porosity of the coating.
[0176] Examples 9 to 12 provide examples of coatings prepared by the preparation method of the above examples under different micro-arc oxidation treatment parameters, in which the electrolytic components all include: 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0177] Example 9
[0178] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0179] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0180] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 0.7A, the duty cycle was 20%, the frequency was 250Hz, and the processing time was 15min. The SEM image of the obtained coating is shown in the figure below. Fig.15 shown.
[0181] Example 10
[0182] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0183] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0184] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 0.7A, the duty cycle was 35, the frequency was 400Hz, and the processing time was 25min. The SEM image of the obtained coating is shown in the figure below. Fig.16 shown.
[0185] Embodiment 11
[0186] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0187] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0188] The foamed aluminum was placed in the electrolyte as the anode, and the unipolar pulse output mode was used. The positive current was 1.0A, the duty cycle was 35%, the frequency was 550Hz, and the processing time was 15min. The SEM image of the obtained coating is shown in the figure below. Fig.17 shown.
[0189] Example 12
[0190] Foamed aluminum is used as the matrix. The components of the electrolyte include 10 g / L sodium silicate, 10 g / L sodium tetraborate and 1 g / L sodium hydroxide.
[0191] Prepare the electrolyte: first add 2L of deionized water into a beaker, start stirring, then add each component of the electrolyte in turn, stir for 2 hours, and all solutes are dissolved and mixed evenly.
[0192] The foamed aluminum was placed in the electrolyte as the anode, and a unipolar pulse output mode was used with a positive current of 1.6A, a duty cycle of 35%, a frequency of 250Hz, and a processing time of 5min. The SEM image of the obtained coating is shown in the figure below. Fig.18shown.
[0193] Combination Figures 15 to 18 As shown, by adjusting the parameters of the micro-arc oxidation treatment, the pore size and distribution of the coating can be controlled, thereby achieving the adjustment of the porosity.
[0194] Example 13 shows an example of preparing the coating using a two-step method as a whole.
[0195] Embodiment 13
[0196] The substrate is a foamed aluminum substrate, the functional component is titanium dioxide, and the multi-level porous functional coating is prepared by the preparation method of the multi-level porous functional coating described in any of the above embodiments. The specific steps are as follows:
[0197] First, prepare a first electrolyte, which includes: 10 g / L sodium silicate, 10 g / L sodium tetraborate, and 1 g / L sodium hydroxide.
[0198] After preparing the dosage of each component, the first electrolyte was prepared by adding 2L of deionized water into a beaker, stirring was started, sodium silicate, sodium tetraborate and sodium hydroxide were added in sequence, and stirring was performed for 2 hours to dissolve all the solutes and mix them evenly.
[0199] The pretreated aluminum foam substrate was placed as an anode in the first electrolyte, and a unipolar pulse output mode was used. The working parameters were set as follows: positive current was 1.0 A, duty cycle was 35%, frequency was 550 Hz, and processing time was 8 min to obtain a multi-level porous coating.
[0200] Then, prepare the second electrolyte, which includes: 10 g / L sodium silicate, 10 g / L sodium tetraborate, 1 g / L sodium hydroxide, 10 ml / L ethylene glycol, 15 ml / L triethanolamine, and 1 g / L carbon dioxide, wherein the particle size of the carbon dioxide is nanometer level.
[0201] After preparing the dosage of each component, prepare the second electrolyte. Prepare two beakers with a capacity of 1L. In one cup, add 1L of deionized water, sodium silicate, sodium tetraborate, and sodium hydroxide in turn, and stir for 1 hour. In the second cup, add 1L of deionized water, ethylene glycol, triethanolamine, and nano-titanium dioxide in turn, and ultrasonically mature in a constant temperature ultrasonic cleaning machine for 1 hour. The temperature is set to 20°C (in actual application, it is selected and set below 30°C according to actual conditions) to ensure that the catalyst particles are evenly dispersed. Finally, mix the two cups of solution and continue stirring for 1 hour to complete the configuration of the second electrolyte.
[0202] Micro-arc oxidation treatment was performed. The foamed aluminum substrate with the multi-level porous coating was placed in the second electrolyte as the anode, and the unipolar pulse output mode was used. The working parameters were set as follows: positive current was 1.0A, duty cycle was: 35%, frequency was 550Hz, and treatment time was 15min to obtain a multi-level porous functional coating.
[0203] Combination Fig.19 and Fig. 20 Shown are the image of the coating prepared in this example and the EDS (Energy Dispersive X-ray Spectroscopy) scanning image made under TEM (Transmission Electron Microscopy). It can be seen from the image that the porosity of the coating is relatively high, and the catalyst particles are adsorbed on the outside of the coating and inside the pores, thereby improving the catalytic efficiency of the coating.
[0204] Comparative Example 7
[0205] In the comparative example, titanium dioxide is used as the functional component, and the coating preparation step adopts the "one-step method" operation steps, which are as follows:
[0206] Prepare an electrolyte, which includes: 10 g / L sodium silicate, 10 g / L sodium tetraborate, 1 g / L sodium hydroxide, 10 ml / L ethylene glycol, 15 ml / L triethanolamine, and 1 g / L carbon dioxide, wherein the particle size of the carbon dioxide is nanometer level.
[0207] After preparing the dosage of each component, prepare the electrolyte. Prepare two beakers with a capacity of 1L. In one cup, add 1L of deionized water, sodium silicate, sodium tetraborate, and sodium hydroxide in turn, and stir for 1 hour. In the second cup, add 1L of deionized water, ethylene glycol, triethanolamine, and nano-titanium dioxide in turn, and ultrasonically mature in a constant temperature ultrasonic cleaning machine for 1 hour. The temperature is set to 20°C (in actual application, it is selected and set below 30°C according to actual conditions) to ensure that the catalyst particles are evenly dispersed. Finally, mix the two cups of solution and continue stirring for 1 hour to complete the configuration of the electrolyte.
[0208] The foamed aluminum was placed in the electrolyte as an anode, and a unipolar pulse output mode was used. The working parameters were set as follows: positive current was 1.0 A, duty cycle was 35%, frequency was 550 Hz, and processing time was 23 min to obtain a coating.
[0209] Combination Fig.21 and Fig. 22 Shown are an image of the coating prepared in this example and an EDS scanning image taken under TEM. From the image, it can be seen that the pores of the coating have basically disappeared, and along the thickness direction of the coating, the catalyst particles are evenly distributed in the coating, which reduces the catalytic efficiency.
[0210] By comparing Example 13 with the above-mentioned Comparative Example 7, the analysis is as follows:
[0211] In the embodiment of the present disclosure, a two-step method is used to prepare the coating. The first step is to use a foamed aluminum substrate and a first electrolyte, and adopt a micro-arc oxidation technology, and the treatment time is 8 minutes to prepare a multi-level porous coating. The second step is to use a foamed aluminum substrate with a multi-level porous coating and a second electrolyte, and adopt a micro-arc oxidation technology, and the treatment time is 15 minutes to prepare a multi-level porous functional coating.
[0212] In the comparative example, the coating was prepared in a one-step method, directly using the foam aluminum substrate and the second electrolyte, and adopting the micro-arc oxidation technology. The processing time was 23 minutes to prepare the multi-level porous coating.
[0213] By comparison, it can be seen that the disclosed embodiment retains the pore structure of the coating through a two-step method, so that the catalyst particles are not only distributed on the surface of the coating, but also can enter the inside of the pores, thereby improving the catalytic efficiency of the coating. In the comparative example, the foamed aluminum matrix is directly used. Moreover, when the total treatment time of the micro-arc oxidation technology is the same, compared with Example 13, the comparative example has a longer treatment time for titanium dioxide, which leads to the disappearance of the pores of the coating, and the excessive time causes carbon dioxide to penetrate into the interior of the coating, affecting the catalytic efficiency.
[0214] The embodiments of the present disclosure are sufficiently illustrated by the description and drawings to enable those skilled in the art to practice them. Other embodiments may include structural and other changes. The embodiments represent only possible variations. Unless expressly required, individual components and functions are optional, and the order of operations may vary. Portions and features of some embodiments may be included in or replace portions and features of other embodiments. The embodiments of the present disclosure are not limited to the structures described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing a substrate with a multi-level porous coating, characterized in that: include: Placing the substrate in a first electrolyte, and using the substrate as an anode and stainless steel as a cathode, performing a first micro-arc oxidation treatment to obtain a substrate with a multi-level porous coating; The components of the first electrolyte include sodium silicate, sodium tetraborate and sodium hydroxide.
2. The preparation method according to claim 1, characterized in that: The mass concentration of each component in the first electrolyte is as follows: The mass concentration of sodium silicate ranges from 5 g / L to 15 g / L, the mass concentration of sodium tetraborate ranges from 5 g / L to 15 g / L, and the mass concentration of sodium hydroxide ranges from 1 g / L to 3 g / L.
3. The preparation method according to claim 1, characterized in that: The ratio of the mass concentration of sodium silicate to the mass concentration of sodium tetraborate ranges from 0.33 to 3.
4. The preparation method according to claim 1, characterized in that: The configuration method of the first electrolyte includes: Adding sodium silicate, sodium tetraborate and sodium hydroxide into a solvent and stirring for a set time to obtain a first electrolyte; Preferably, the solvent is selected from at least one of deionized water and pure water.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The steps of performing the first micro-arc oxidation treatment include: The pre-processed substrate is processed according to a first preset current, a first preset duty cycle and a first preset frequency, using a preset pulse processing method and a first preset duration.
6. The preparation method according to claim 5, characterized in that: The preset pulse processing modes include: unipolar pulse output mode or bipolar pulse output mode; The value range of the first preset current is: 0.7A to 2.0A; and / or, The first preset duty cycle has a value range of 5% to 40%; and / or, The first preset frequency has a value range of 100 Hz to 1000 Hz; and / or, The value range of the first preset time length is: 5min to 40min.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method further comprises: The obtained substrate with the multi-level porous coating is used as an anode, placed in a second electrolyte, and stainless steel is used as a cathode to perform a second micro-arc oxidation treatment to obtain a multi-level porous functional coating; The components of the second electrolyte include: sodium silicate, sodium tetraborate, sodium hydroxide and functional components; Preferably, the step of configuring the second electrolyte comprises: Deionized water, sodium silicate, sodium tetraborate and sodium hydroxide are added into the first container and stirred for a second period of time to obtain a first reserve solution.
8. The preparation method according to claim 7, characterized in that: The proportions of the components in the second electrolyte are as follows: the mass concentration of sodium silicate ranges from 5 g / L to 15 g / L, the mass concentration of sodium tetraborate ranges from 5 g / L to 15 g / L, the mass concentration of sodium hydroxide ranges from 1 g / L to 3 g / L, and the mass concentration of the functional component ranges from 3 g / L to 8 g / L; and / or, The functional component is selected from at least one of titanium dioxide, copper oxide and zinc oxide.
9. The preparation method according to claim 7, characterized in that: The components of the second electrolyte also include: ethylene glycol and triethanolamine; In the second electrolyte, the mass concentration of ethylene glycol ranges from 5 ml / L to 15 ml / L, and the mass concentration of triethanolamine ranges from 10 ml / L to 20 ml / L; Preferably, the step of configuring the second electrolyte further comprises: Adding the solvent, ethylene glycol, triethanolamine and nano-titanium dioxide into a second container, and performing constant temperature ultrasonic aging for a third period of time to obtain a second reserve solution; The first reserve solution and the second reserve solution are mixed and stirred for a fourth period of time to obtain a second electrolyte solution.
10. The preparation method according to claim 7, characterized in that: The second micro-arc oxidation treatment step includes: using a preset pulse treatment method and a second preset duration according to a second preset current, a second preset duty cycle, and a second preset frequency; Preferably, the second preset current has a value range of: 0.7A to 2.0A; and / or, Preferably, the second preset duty cycle has a value range of 5% to 40%; and / or, Preferably, the second preset frequency has a value range of 100 Hz to 1000 Hz; and / or, Preferably, the second preset time length ranges from 10 minutes to 20 minutes.
11. The preparation method according to claim 7, characterized in that: The temperature of the first electrolyte and / or the second electrolyte is less than or equal to 10° C.; and / or, The matrix material includes foamed aluminum, aluminum alloy or magnesium alloy.
12. A catalyst carrier, characterized in that: include: The substrate is prepared by the method for preparing a substrate with a multi-level porous functional coating as described in any one of claims 1 to 11.
13. A device using the catalyst carrier according to claim 12.